Performance evaluation of FH-OCDMA in the presence of GVD and SPM - Ng, Wai Ling; Abbou, F. M.; Abid, A.; Chuah, Hean Teik (The Institute of Electronics, Information and Communication Engineers, 2005)
Performance analysis is carried out to evaluate Frequency-Hopping Optical Code Division Multiple Access (FH-OCDMA) in the presence of group velocity dispersion (GVD) and self-phase modulation (SPM). It is found that the system suffers higher power penalty as the dispersion increases. At a distance of 200-km the power penalty is reduced to 1 dB for DSF and to approximately 7 dB for SMF when SPM is included. The SMF without SPM suffers the highest power penalty of 6.7 dB at 100-km and 9.5 dB at 200-km.